Avaliação sazonal da qualidade seminal a fresco, refrigerado e pós-descongelação de touros Nelore - Francisquini , Camila Dutra de Souza (2018)
In regions of tropical climate, mating occurs during warmer months, bulls are subject to environmental variations that interfere with their fertility and reproductive efficacy of the herd. The use of some biotechnologies contributes to the efficiency of the production system and to evaluate the fertilization potential of a semen sample, be it fresh, chilled or frozen. A combination of several analyzes and seminal assay methods offers greater accuracy to define a complex functionality. For Chapter 1, the objectives of the study were: (1) to evaluate the effect of the seasons on the surface temperature of the scrotum and ocular globe, the semen quality and plasma concentration of testosterone from Nellore bulls raised extensively, (2) to verify the plasma protein composition (3) investigate the relationships of these proteins with seminal parameters, surface temperatures of the scrotum and THI. Nellore bulls (n = 20) were evaluated with two data collections with a 30-day interval within each season of the year. Infrared thermography (FLIR E40®) with image analysis (FLIR tools software) for spermatic cord (SCT), proximal pole of the testis (PPT), distal pole of the testis (DPT), tail of the epididymis (TeT) and scrotal temperature gradient (TG), and semen collected and analyzed for quantitative and qualitative characteristics. Blood samples were collected by venipuncture of the jugular to obtain the plasma concentration of testosterone by radioimmunoassay (RIA). The seminal plasma proteins were identified by electrophoresis on SDS-PAGE. The temperature-humidity index (THI) calculated per season. The TG was higher (P <0.05) in autumn (5ºC) and winter (4.4ºC) compared to spring (3.4ºC) and summer (3.7ºC). The THI of spring (73.5) and summer (72) differed (P <0.05) from autumn (64.5) and winter (59.6) and there were correlations (P <0.01) with SCT (0.54), TeT (0.74), PPT (0.71), DPT (0.72) and TG (-0.35). Similarly, MOT (61.5%) and VIG (2.7) in spring were lower in relation to autumn and winter (P <0.05). The plasma concentration of testosterone was higher (P <0.05) in the autumn, in relation to the other seasons of the year. Seminal plasma proteins of 20, 55 and 66KDa contributed positively to seminal quality. The concentration of the protein with 50KDa was high in all seasons, being considered indispensable for the fertility of the bulls. In the spring and summer seasons, in which the THI exceeded the value of 72, there was a decrease in progressive motility and spermatic vigor. The summer and fall, the seasons that presented greater percentages of major and total sperm defects. Ocular globe and scrotal surface temperatures increased in spring and summer and the thermal gradient and testosterone plasma concentration decreased in the same seasons, concluding that the thermal stress with THI above 72 in the spring and summer seasons was sufficient for negatively affect the reproduction of Nelore bulls raised in pasture in the tropics. The chapter 2, the objectives of the study were: (1) assess the quality of refrigerated beef semen transported by 3 hours, passive systems of transport of semen BotuBOX® and BotuFLEX®, diluted in TRIS and BotuBOV®; and (2) evaluate the spermatic kinetics, oxidative stress, mitochondrial potential and cell membrane integrity and acrossomal bovine semen after thawing, diluted in TRIS and BotuBOV® and transported in passive systems semen transport BotuBOX® and BotuFLEX®. The six bulls semen of Nellore breed (Bos taurus indicus), cooled and frozen in 2 extenders TRIS and BotuBOV® and transported in 2 cooling systems BotuBOX® and BotuFLEX®. In a semen sample refrigerated was made a subjective analysis of motility (MOT) and sperm vigor (VIG) and in the sample frozen-thawed, computer-assisted sperm analysis (CASA) and flow cytometry, evaluation of integrity of plasma membrane and acrossomal (IPAM), production of superoxide (O2-) and integrity of cells (IC). On after cooled analysis, the MOT of semen in the BotuBOV® and BotuFLEX® (69.4%) and TRIS and BotuFLEX® (62.9%), were higher (P < 0.05) when compared to the TRIS and BotuBOX®. The largest (P < 0.05) MOT (45.9%) observed in subjective analysis, TM (47.3%) and PM (37%) in the CASA, IPAM (29%), IC (19.8%) and lower production of the O2- (82%) found in the samples frozen-thawed diluted in BotuBOV® extender and transported in the BotuFLEX® system. We conclude that the diluted semen in the BotuBOV® and transported on BotuBOX® or BotuFLEX®, and diluted TRIS extender and transported on BotuFLEX® maintained the viability for using the cooled semen, as well as employment for freezing. The association between the BotuBOV® diluent and refrigerated transport of semen BotuFLEX® presented best effect on the frozen semen in regard to kinetics parameters, integrity of plasma and acrossomal membranes and oxidative stress reduction.